Thermally induced structural evolution and performance of mesoporous block copolymer-directed alumina perovskite solar cells. - Tan, K; Moore, D; Saliba, M; Sai, H; Estroff, L; Hanrath, T; Snaith, H; Wiesner, U (American Chemical Society, 2014)
Structure control in solution-processed hybrid perovskites is crucial to design and fabricate highly efficient solar cells. Here, we utilize in situ grazing incidence wide-angle X-ray scattering and scanning electron microscopy to investigate the structural evolution and film morphologies of methylammonium lead tri-iodide/chloride (CH3NH3PbI(3-x)Cl(x)) in mesoporous block copolymer derived alumina superstructures during thermal annealing. We show the CH3NH3PbI(3-x)Cl(x) material evolution to be characterized by three distinct structures: a crystalline precursor structure not described previously, a 3D perovskite structure, and a mixture of compounds resulting from degradation. Finally, we demonstrate how understanding the processing parameters provides the foundation needed for optimal perovskite film morphology and coverage, leading to enhanced block copolymer-directed perovskite solar cell performance.